Employ of technology in education: the primary teacher and their basics skill in technology in mathematics classroom - Morales-López, Yuri (2015)
The appropriate and intelligent use of technology resources is essential for the development of a country. This research focuses on competencies of elementary educators about technology resources and how they use it in mathematics classroom. The objective is to describe a sample of Elementary teachers and, thus, obtain evidence regarding to the teachers knowledge about ICT, mainly for management of technological resources into mathematics classroom. This is a preamble to define specific routes for lifelong learning and training for Elementary teachers in Costa Rica. The results indicate that many teachers do not develop basic skills in the use of ICT in the initial training or in the training of the Ministerio de Educación Pública in this issue are not necessarily being translated into relevant training for educators.